NAFKAH RUMAH TANGGA DALAM PERSPEKTIF HUKUM ISLAM - Abdul Fatakh (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2018)
AbstractThe problem of living in domestic life is very important.  Household problems arise due to understanding and paying a living that is not ideal. For example, the disappearance of responsibility, affection, love, to the point of divorce. In fact, the divorce, though lawful, is an act that is hated by Allah ta'ala.In this simple article, the author will explore thoroughly the problem maintenance from the perspective of Islamic law by referring to the opinions of scholars who trusted. Will stick because the issue of the concept of livelihood in Islam is very wide and to obtain a more focused and deeper description, then the above theme is limited only to the discussion about the scholars' view of the law of livelihood.Keywords: Livelihood, Mahar, Wife, Husband AbstrakPersoalan nafkah dalam kehidupan rumah tangga sangat penting. Tidak jarang permasalahan rumah tangga bermunculan akibat pemahaman dan pembayaran nafkah yang tidak ideal. Misalnya, menghilangnya rasa tanggungjawab, rasa sayang, rasa kasih, hingga sampai berujung pada perceraian. Padahal, perceraian itu, meski halal, merupakan tindakan yang dibenci Allah ta’ala. Dalam artikel sederhana ini penulis akan mengupas tuntas pesoalan nafkah dalam perspektif hukum Islam dengan merujuk pendapat-pendapat ulama yang mu’tabar. Akan tetapi karena persoalan mengenai konsep nafkah dalam Islam sangat  luas  dan untuk memperoleh uraian yang lebih fokus dan mendalam,  maka tema di atas dibatasi hanya pada pembahasan seputar  pandangan ulama tentang hukum nafkah.Kata kunci: Nafkah, Mahar, Isteri, Suami